2023
DOI: 10.1186/s12888-022-04501-1
|View full text |Cite
|
Sign up to set email alerts
|

Features and effects of computer-based games on cognitive impairments in children with autism spectrum disorder: an evidence-based systematic literature review

Abstract: Introduction Children with Autism Spectrum Disorder (ASD) have different cognitive and intelligence profiles than typical developing individuals. Some of these children need cognitive rehabilitation. This study's main purpose is to provide a systematic review about applying computerized cognitive games for autistic children and to determine the effectiveness of such interventions. Material and methods A thorough search of the ISI Web of Science, Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 73 publications
0
2
0
3
Order By: Relevance
“…We seek to apply our application with participants with cognitive defects such as parkinsonism, autism, Alzheimer’s, and so forth. For example, some studies have already shown that suitable computerized game-based solutions can improve cognition in children with autism [ 54 , 55 ]. The design of goal-oriented memory strategy programs can significantly improve cognitive functioning as well as performance of activities of daily living and quality of life in people with cognitive impairments [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…We seek to apply our application with participants with cognitive defects such as parkinsonism, autism, Alzheimer’s, and so forth. For example, some studies have already shown that suitable computerized game-based solutions can improve cognition in children with autism [ 54 , 55 ]. The design of goal-oriented memory strategy programs can significantly improve cognitive functioning as well as performance of activities of daily living and quality of life in people with cognitive impairments [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figura 1. Melhorias cognitivas mencionadas por número de artigos de revisão Além destes, outros resultados cognitivos positivos com menções únicas a se destacar foram: melhora na coordenação olho-mão [Kokol et al, 2020]; ativação de áreas dos córtex pré-frontal, pré-motor, parietal e de associação visual e das áreas temporais do cérebro, bem como sucesso no ensino de novas habilidades [Silva et al, 2021]; e melhora na reação a processos aleatórios, no processamento de informações paralelas e na qualidade de vida [Rezayi, Tehrani-Doost & Shahmoradi, 2023].…”
Section: Sobre Como São Aplicados Os Jogos Digitais Usados No Apoio A...unclassified
“…Graças a adoção do uso de jogos digitais para apoio ao TEA, já existem diversas revisões sobre o tema, mas observando algum nicho de jogo específico, como [Milajerdi, Ordooiazar & Dewey, 2023], que buscam apenas jogos sérios, e [Rezayi, Tehrani-Doost & Shahmoradi, 2023], que focaram em jogos para computador, ou buscando jogos em que se investigou alguma característica específica do TEA, como [Hassan, Pinkwart & Shafi, 2021] que pesquisaram jogos sérios que visavam melhorar as inteligências social e emocional. Ainda, algumas revisões observam o uso de jogos digitais no apoio de mais de uma dificuldade física ou neurológica além do TEA, como [Tsikinas & Xinogalos, 2019], que discutem jogos para pessoas com TEA ou com deficiências intelectuais.…”
Section: Introductionunclassified
“…GBL merupakan media pembelajaran yang diyakini mampu membuat siswa konsentrasi (Mulyati, 2023), memotivasi siswa untuk (Bassiouni et al, 2019;Khaleghi et al, 2021;Martins et al, 2022;Novayani, 2022;Saputra et al, 2019;Spatioti et al, 2022). Selain itu, belajar melalui game membuat siswa senang dan tertarik (Novayani et al, 2021) dalam memainkannya, juga meningkatkan keterlibatan siswa dalam belajar (Arif et al, 2019;Bolat & Taş, 2023;Nadeem et al, 2023), dan dapat meningkatkan kemampuan siswa (Mardhotillah & Rakimahwati, 2021), membuat siswa lebih aktif (Ulumudin & Sujatmiko, 2023) dan meningkatkan kognitif siswa pada siswa autis (Rezayi et al, 2023). Game edukasi diyakini efektif dibandingkan dengan metode konvensional (Bassiouni et al, 2019).…”
Section: Pendahuluanunclassified